Analisis Strategi Pemasaran Dalam Menghadapi Persaingan Usaha Terhadap Usaha Ikan Laut - Dora Rinova; Delah Gapur (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
The existence of potential fishery resources in Indonesia makes business opportunities very abundant and profitable. This is a result of the large number of people consuming marine fish and the increasing demand for marine fish in the market resulting in intense competition in the business. The purpose of this research is to identify the implementation of the marketing strategy of marine fish agents in the Bandar Jaya Timur market, to find out the competitive conditions of marine fish agents and to find out how marine fish agents in the East Bandar Jaya Market face business competition. The type of research used is a qualitative research method with a descriptive design. The results of the research prove that the result of strength with opportunity and SO (Strength Opportunities) strategy, so that it is found that the aspect that must be prioritized is the quality of the product by looking at the increasing purchasing power of the people. The next result is that weaknesses and opportunities or WO (Weakness-Opportunity) strategies are found to take advantage of opportunities for increasing public purchasing power and increasing the number of human resources, as well as optimizing the schedule for fishing. Internal and external analysis of the industry and Cartesian diagrams can be found that the main strategy of the marine fish business is the Growth strategy. The marine fish business can maintain and improve the quality of marine fish products so that people continue to believe in the products of the marine fish business and establish networks with suppliers and consumers as well as expand marketing and take advantage of technological developments to face business competition.